COLLATERAL DAMAGE AND COLLATERAL HEALING IN OUR AMERICAN INDIAN COMMUNITIES WHAT NEEDS TO OCCUR AND WHERE TO BEGIN - Morris, Jesse J. (European Scientific Journal, ESJ, 2014)
In the following article the authors will be discussing society’s current view and tolerance in regards to alcohol and substance use. Discussion will focus on the current belief system in regards to what is influencing this acceptance. The impact and outcome of this apathy will then be discussed in relation to Collateral Damage via statistics and examples. Discussion will further focus on Collateral Damage in the American Indian population what role will and can treatment play in this. Introduced will be the topic of Collateral Healing from the belief that if the user/abuser is creating Collateral Damage with their usage then the most appropriate method of intervention would be Collateral Healing.